Letramento digital : desafios na formação universitária no curso de Letras da UEG-Campus Porangatu - (:unkn) unknown (Universidade Estadual de Goiás, 2019)
In this research, we aimed to understand the extent to which participants broadened the understanding of digital literacy from the discussions in the rodas de Conversa in order to verify if they are able to act in the development of digital literacy events in their future teaching activity. This is a study of qualitative interpretative nature (Erickson, 1990) carried out with academics of the Curso de Letras. We know that the process of globalization has further accelerated the development of technologies and has directly impacted people's social, cultural, political, economic and educational lives. Therefore, in the search for an understanding of this complex reality of today's world, the establishment of discussions of texts, passages, and citations, which were intended to enable academics to have or broaden the understanding of digital literacy to act appropriately with the resources coming of digital technologies, or at least consider them in their everyday practices. These assumptions favor the problematization and, consequently, the application of pedagogical practices adequate for the production of knowledge in the attempt to change the reality of the individuals involved and reverberate in effective actions. Moreover, since digital literacy is a socially and culturally situated practice, it allows individuals to read, read the world and themselves, respecting their subjectivity and identities while valuing otherness and empathy. Thus, with innovations in the labor market, the sociotechnical concept emerges (SIGNORINI; CAVALCANTI, 2010) and with it the idea of design (COPE; KALANTZIS, 2000; LEFFA, 2017), which has its effects amplified by the resources of the multimodal language (COPE; KALANTIZ, 2009). In order to understand the impacts of the technologies, we enlisted to the pedagogy of multiliteracies (COPE; KALANTZIS, 2006; ROJO, 2012, 2013), the multiple literacy theory (MASNY, 2010) – embodied in the plural character of practices, always procedural – and the contingency, instantiated by the movement of becoming. For this purpose, digital literacy emerges (BUZATO, 2006; MONTE MÓR, 2017; SABOTA, 2017), which favors the use of digital technologies beyond the instrumental and technical concept by allowing a critical and reflective agency positioning. To do so, in order to unveil effective pedagogical practices, we bring theoretical considerations about the teacher education in the initial stage for the TDIC (SABOTA 2017, MENEZES DE SOUZA, 2011; BRAGA, 2007), as well as the concept of liquid modernity (BAUMAN, 2001) and digital culture (SANTAELLA, 2005, 2007). In analyzing the empirical material, we perceive that the participants present an approximation regarding the use, which is more instrumental and technical and less reflective. Already in relation to the concept, there is in the group who presents reflection, problematizations and the understanding that is in agreement with the understanding of what will become the digital
Keywords: Tecnologia digital; Formação inicial de professores; Letramento digital; Digital technology; Initial teacher education; Digital literacy; CIENCIAS HUMANAS::EDUCACAO